Dynamic Microbiome Changes Reveal the Effect of 1-Methylcyclopropene Treatment on Reducing Post-harvest Fruit Decay in “Doyenne du Comice” Pear - Zhang, Yang; Gao, Congcong; Masum, Md. Mahidul Islam; Cheng, Yudou; Wei, Chuangqi; Guan, Yeqing; Guan, Junfeng (Frontiers in Microbiology, 2021)
Pathogen-induced decay is one of the most common causes of fruit loss, resulting in substantial economic loss and posing a health risk to humans. As an ethylene action inhibitor, 1-methylcyclopropene (1-MCP) can significantly reduce fruit decay, but its effect on fruit pathogens remains unclear. Herein, the change in microbial community structure was analyzed using the high-throughput sequencing technology, and characteristics related to fruit quality were determined after 1-MCP (1.0 M l L–1) treatment in “Doyenne du Comiceis” pear fruit during storage at ambient temperature. Overall, 1-MCP was highly effective in reducing disease incidence and induced multiple changes of the fungal and bacterial microbiota. At day 15, the microbial diversity of fungi or bacteria was reduced significantly in the control fruit (non-treated with 1-MCP), which had the most severe decay incidence. For fungi, in addition to Alternaria being the most abundant in both 1-MCP treatment (59.89%) and control (40.18%), the abundances of Botryosphaeria (16.75%), Penicillium (8.81%), and Fusarium (6.47%) increased significantly with the extension of storage time. They became the primary pathogens to cause fruit decay in control, but they were markedly decreased in 1-MCP treatment, resulting in reduced disease incidence. For bacteria, the abundance of Gluconobacter (50.89%) increased dramatically at day 15 in the control fruit, showing that it also played a crucial role in fruit decay. In addition, Botryosphaeria, Fusarium fungi, and Massilia, Kineococcus bacteria were identified as biomarkers to distinguish 1-MCP treatment and control using Random Forest analysis. The redundancy analysis (RDA) result showed that the amount of Botryosphaeria, Penicillium, and Fusarium were positively correlated with disease incidence and respiration rate of pear fruits while negatively correlated with fruit firmness. This investigation is the first comprehensive analysis of the microbiome response to 1-MCP treatment in post-harvest pear fruit, and reveals the relationship between fruit decay and microbial composition in pear fruit.